OPTIC: orthologous and paralogous transcripts in clades - Heger, A; Ponting, C (Oxford University Press, 2009)
The genome sequences of a large number of metazoan species are now known. As multiple closely related genomes are sequenced, comparative studies that previously focussed on only pairs of genomes can now be extended over whole clades. The orthologous and paralogous transcripts in clades (OPTIC) database currently provides sets of gene predictions and orthology assignments for three clades: (i) amniotes, including human, dog, mouse, opossum, platypus and chicken (17443 orthologous groups); (ii) a Drosophila clade of 12 species (12889 orthologous groups) and (iii) a nematode clade of four species (13626 orthologous groups). Gene predictions, multiple alignments and phylogenetic trees are freely available to browse and download from http://genserve.anat.ox.ac.uk/clades. Further genomes and clades will be added in the future.